2009
DOI: 10.26530/oapen_503833
|View full text |Cite
|
Sign up to set email alerts
|

Global Change and Sustainable Development in Mountain Regions – Proceedings of the COST Strategic Workshop

Abstract: This publication is supported by COST.The legal notice by COST Office: Neither the COST Office nor any person acting on its behalf is responsible for the use which might be made of the information contained in this publication. The COST Office is not responsible for the external websites referred to in this publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 78 publications
0
2
0
2
Order By: Relevance
“…As a consequence of a major transformation in the region's landuse system after 1990, followed by changes in private land ownership, LC transitions (LCTs) are observed over extensive areas of the Carpathians and typically result in farmland abandonment and gradual forest expansion (Björnsen Gurung et al, 2009). On the other hand, rapid urban sprawl connected mainly with tourism development is noted at many sites in PC (Kozak, 2009). As some transitions in LC (e.g., conversion of natural areas or productive farmland to settlements, or deforestation of forest with high conservation value) may be universally agreed as negative LC change (LCC; Cowie et al, 2018), the observed LCTs give rise to a question about the current LDN status for the PC, including each biophysical unit (catchment) involved.…”
Section: )mentioning
confidence: 99%
“…As a consequence of a major transformation in the region's landuse system after 1990, followed by changes in private land ownership, LC transitions (LCTs) are observed over extensive areas of the Carpathians and typically result in farmland abandonment and gradual forest expansion (Björnsen Gurung et al, 2009). On the other hand, rapid urban sprawl connected mainly with tourism development is noted at many sites in PC (Kozak, 2009). As some transitions in LC (e.g., conversion of natural areas or productive farmland to settlements, or deforestation of forest with high conservation value) may be universally agreed as negative LC change (LCC; Cowie et al, 2018), the observed LCTs give rise to a question about the current LDN status for the PC, including each biophysical unit (catchment) involved.…”
Section: )mentioning
confidence: 99%
“…According to climate scientists, storms and winds that cause the effect of wind will occur more frequently by the year 2050 compared to the present day (García-Casals, 2008;Jandl et al, 2009). Adequate preparation is necessary to mitigate the damages caused by windthrow.…”
Section: Introductionmentioning
confidence: 99%
“…These emerging developments have led to the depletion of critical natural resources, impacting the natural environment and basic ecosystems services. This is particularly the case for increased incidences of water shortage from the drying of water sources and the increasing vulnerabilities of rural communities, particularly the poor and the groups vulnerable to food and livelihood security (Jandl et al , 2009). In these scenarios, achieving food security, economic development and biodiversity goals seems a distant dream, particularly with the additional challenges presented by global climate change.…”
Section: Introductionmentioning
confidence: 99%